Performance of Daily Pads Containing Ophytrium and Chlorhexidine Digluconate 3% in Dogs With Local Cutaneous Bacterial and/or Malassezia Overgrowth - Gatellet, Marina; Kesteman, Roxane; Baulez, Benjamin; Pradiès, Félix; Cadot, Pierre-Marie; Dropsy, Hélène; Fiora, Pierre; Mathet, Jean-Loup; Ollivier, Elodie; Billy, Charlotte; Zemirline, Claudine; De Jaeger, Xavier (Frontiers in Veterinary Science, 2021)
Local disturbances of the microbiota are common in dogs with underlying skin conditions. Antiseptic topical products are indicated to control such superficial disorders. The objective of this study was to evaluate the performance of a daily application of pads containing Ophytrium and chlorhexidine digluconate 3% (DOUXO® S3 PYO Pads, Ceva Santé Animale, France) in dogs with focal bacterial and/or Malassezia overgrowth. Eighteen dogs with focal skin dysbiosis were included in the analysis of this prospective, multicentric, field study. Dogs received daily pad applications for 14 days. Bacterial and/or Malassezia counts per microscopic field and a global score of the most affected patch (0–17 scale based on extension, severity, bacterial, and Malassezia cytological scores) were assessed by a veterinarian and pruritus by the owner (Pruritus Visual Analog Scale) on days (D)0, D7, D14. Owner and veterinarian evaluations for performance and satisfaction were recorded. Eleven dogs had primarily cocci overgrowth and seven mostly Malassezia. Mean bacterial and Malassezia counts decreased after 14 days (6.9–1.1; 7.6–1.5, respectively); 88.9% of dogs achieved a ≥70% microbial decrease and had ≤2 bacteria and ≤1 Malassezia per oil field. Mean global score of the most affected patch and pruritus score significantly improved at D14, respectively, from 8.6 to 2.6 and 4.5 to 1.2 (P < 0.05 each, mean improvements of 70.4 and 71.4%, respectively). Global veterinary assessment of the protocol was satisfactory, good, or excellent in 88.9% of cases. Most owners (94.4%) considered the protocol efficacious. Using a pad containing Ophytrium and chlorhexidine digluconate 3% daily for 14 days improved the skin condition and pruritus of dogs with local dysbiosis, resulting in high satisfaction levels for both veterinarians and dog owners.